Nutritional support practices among intensive care unit (ICU) patients, observational study - May Hamdan; Fatima Al-Amouri; Ayat Ali Abu-fara; Mai Qasem Heih; Fatima Ibrahim Manasrah; Hanan Alaa Abu-shamsyh; Manal Badrasawi (Clinical Nutrition Open Science)
Summary: Background and Aims: Critically ill patients are at high risk of mortality, morbidity, and poor outcomes. Therefore, nutritional support is the standard care to avoid related complications and improve health outcomes. The aim of this study is to identify feeding practices among ICU patients, evaluate their nutritional adequacy, and assess the prevalence of malnutrition and its associated factors. Methods: This observational study involved 106 ICU patients in three hospitals at Hebron/Palestine. An interview-based questionnaire was used to collect data related to sociodemographic, lifestyle, ICU-related data, medical history, clinical outcomes, physical examination, energy, and protein consumption. Malnutrition was evaluated using the malnutrition universal screening tool (MUST), and biochemical data were recruited from patients' medical records. Results: Among study participants aged 18–99 years (63.69 ± 20.48), enteral feeding was the predominant route among 51.9 %, and nutritional support was initiated two days after ICU admission. In addition, 91.5 % and 67 % of patients failed to receive their nutritional requirements of energy and protein, respectively. The malnutrition universal screening tool revealed that 53.8 % of ICU patients were at low risk of malnutrition, 20.8 % were at medium risk, and 25.5 % were at high risk of malnutrition, while lower energy consumption contributed significantly to the higher risk of malnutrition among ICU patients. Conclusion: The study found that enteral feeding is the main nutritional support in ICU patients, but energy and protein intake are insufficient. Despite early feeding, malnutrition rates are high and linked to lower calorie intake, emphasizing the need for better nutritional screening and interventions to improve patient outcomes.